An old journal for new challenges - Bertazzi, Pier Alberto (La Medicina del Lavoro, 2020)
As of December 2019, I have stepped down from my role as Editor-in-Chief, and I am pleased that Antonio Mutti accepted the invitation by the Italian Society of Occupational Health to become the new Directorof the Journal founded in 1901 by Luigi Devoto with the title “The Work”. The birth of this Journal, at the beginning of the twentieth century, marked the renaissance of the awareness of the close relation linking people’s work to their health, and not just because of accidents. Bernardino Ramazzini, a professor of medicine, had described this link for the first time in the modern era, in a systematic way, in a book edited in Latin in 1700 (De Morbis Artificum Diatriba), which marked the emergence of a new medical, scientific discipline.